Effectiveness Of Unified Approach in Practical Research Through Contextualization - Reynaldo V. Moral (Genius Journals, 2021)
This quasi-experimental study highlights the effectiveness of unified approach in Practical Research through contextualization in Don Sergio Osmeňa Sr. Memorial National High School Grade 11 students. Most of these students appear are required to take the required applied subjects but in a closer examination they are slow in the development of cognitive skills especially in research concepts. A control group is taught, tested and retested the same using the conventional lecture method and without emphasis on contextualization at the same time as the experimental group. Results showed that there are no significant differences on their achievement scores and context related problems with research-oriented and regular students. They are also well inclined at dimension of remembering while least at dimension of creating based on cognitive processes. This suggests that there should be an important value in effective and efficient instruction on the basics of research
Keywords: Cognitive process; contextualization; research; unified approach